2010
DOI: 10.1007/s11250-010-9670-7
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric and mediastinal lymph node infection with Linguatula serrata nymphs in sheep slaughtered in Kerman slaughterhouse, southeast Iran

Abstract: This research was carried out in order to detect the prevalence of nymphal stages of Linguatula serrata in mediastinal and mesenteric lymph nodes of sheep slaughtered in Kerman slaughterhouse, southeast of Iran. For this purpose, mesenteric and mediastinal lymph nodes of 806 sheep of different sex and age were examined. One hundred and thirty out of 806 (16.1%) of the sheep were found positive for L. serrata infection. The infection rate increased with age (P<0.001). Prevalence of L. serrata nymphs in males an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 8 publications
3
10
0
Order By: Relevance
“…Similar findings were reported by other researchers in Iran and Turkey (Tajik et al, 2006;Nourollahifard et al, 2010b;Nourollahifard et al, 2011;Aydenizöz et al, 2012;Alborzi et al, 2013;Nematollahi et al, 2015). Nourollahifard et al (2010) and Sadeghi-Dehkordi et al (2014) reported the prevalence of L. serrata nymphs to be significantly higher in females than in males.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar findings were reported by other researchers in Iran and Turkey (Tajik et al, 2006;Nourollahifard et al, 2010b;Nourollahifard et al, 2011;Aydenizöz et al, 2012;Alborzi et al, 2013;Nematollahi et al, 2015). Nourollahifard et al (2010) and Sadeghi-Dehkordi et al (2014) reported the prevalence of L. serrata nymphs to be significantly higher in females than in males.…”
Section: Discussionsupporting
confidence: 84%
“…In the first step of examination, the prevalence of L. serrata infection were detected 24.81% (100/403) (Rezaei et al, 2012;Youssefi et al, 2012;Sadeghi-Dehkordi et al, 2014;Kheirabadi et al, 2014), 9-52.5% in sheep (Tavassoli et al, 2007a;Nourollahifard et al, 2011;Youssefi et al, 2012;Sadeghi-Dehkordi et al, 2014;Azizi et al, 2015;Kheirabadi et al, 2015), and 14.8-69.1% in cattle (Tajik et al, 2006;Nourollahifard et al, 2010b;Youssefi and Hadizadeh-Moalem, 2010;Rezaei et al, 2011;Youssefi et al, 2012;Alborzi et al, 2013;Nematollahi et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence rates of 11.5%, 52% and 16.1% linguatulosis in sheep have been reported from Fars, Kerman and west Azerbaijan provinces of Iran, respectively Tavassoli et al, 2007;Nourollahi Fard et al, 2011). (Tajik et al, 2006), 16.22% in Kerman eastern Iran (Nourollahi Fard et al, 2010a), 14.8% in Babol northern Iran (Youssefi & Hadizadeh Moalem, 2010), and 0.25% in Tabriz, western Iran (Hami et al, 2009) have previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have been carried out as regards the prevalence of L. serrata infection in animals including, dogs (Meshgi & Asgarian, 2003;Oryan et al, 2008), camels (Pourjafar et al, 2007;Tajik et al, 2007;Shakerian et al, 2008;Oryan et al, 2011), buffaloes (Tajik et al, 2008;Rezaei et al, 2011), sheep Nourollahi Fard et al, 2011), cattle (Hami et al, 2009;Nourollahi Fard et al, 2010a) and goats Nourollahi Fard et al, 2010b) in many parts of Iran, but the incidence of L. serrata in herbivores in western Iran is practically unknown.…”
Section: Introductionmentioning
confidence: 99%